ZNO nanoparticles as saturable absorber for passively Q-switched fiber laser in C-and S-band / Cherrie Lee Sue Jing - Cherrie Lee , Sue Jing (2018)
This work investigates the characteristics of pulses generated via passive Q-switching in S- and C-band using zinc oxide nanoparticles as saturable absorber. Unlike active Q switching, passive Q-switching is a cheaper and simpler alternative to obtain pulses with repetition rates in the range of kilohertz and pulse width of mircoseconds. There are several techniques to obtain passively Q-switched laser such as the employment of nonlinear polarization rotation (NPR), semiconductor saturable absorber (SESAM), carbon-based saturable absorber (single-walled carbon nanotubes (SWCNT), graphene and graphene oxide) and transition metal-dichalcogenides saturable absorber (molybdenum disulfide, molybdenum diselenide, tungsten disulfide and tungsten diselenide). Nanomaterials such as zinc oxide nanoparticles have distinctive optical, electronic and mechanical properties which made them a suitable candidate as a saturable absorber (SA) for passively Q-switched laser. Erbium-doped fiber (EDF) is used as the gain medium in the laser cavity to obtain Q-switched pulses in C-band. C-band is the most commonly used wavelength in optical communications. Due to increasing data traffic, there is a demand to expand the optical network to other bands to reduce network congestion. One of the bands being considered to accommodate this expansion is S-band. Depressed-cladding erbium-doped fiber (DC-EDF) is used as the gain medium in the laser cavity to obtain Q-switched pulses in S-band. The tuning range of these pulses in C-band and S-band are also investigated. The results obtained from this work is instrumental as Q-switched lasers are widely used in many applications such as aesthetic treatment, biomedical diagnostic, remote-sensing and telecommunications.